Opening a window to the acutely injured brain: Simultaneous retinal and cerebral vascular monitoring in rats - Warner, Laura; Bach-Hagemann, Annika; Schmidt, Tobias P.; Pinkernell, Sarah; Schubert, Gerrit A.; Clusmann, Hans; Albanna, Walid; Lindauer, Ute; Conzen-Dilger, Catharina (Frontiers in Molecular Neuroscience, 2023)
Many recent research projects have described typical chronical changes of the retinal vasculature for diverse neurovascular and neurodegenerative disorders such as stroke or Alzheimer’s disease. In contrast to the cerebral vasculature, retinal blood vessels can be assessed non-invasively by retinal vessel analysis. To date, there is only little information about potential simultaneous reactions of retinal and cerebral vessels in acute neurovascular diseases. More information about potential correlations between those two vascular beds and the feasibility of non-invasive retinal vessel analysis in acute neurovascular disease could significantly widen the field of applications of this promising screening tool. Here, we present our protocol for the simultaneous assessment of retinal and cerebral vessels in an acute setting in anesthetized rats using a non-invasive retinal vessel analyzer and a superficial tissue imaging system for laser speckle contrast analysis via a closed bone window. We describe the experimental set-up in detail, outline pitfalls concerning repeated retinal vessel analyzes in an experimental set-up of several hours, and address issues arising from the simultaneous use of two different assessment tools. Finally, we focus on the robustness and variability of the reactivity to hypercapnia of retinal vessels at baseline as well as their reproducibility over time using two narcotic protocols common for neurovascular research.